Alistair Darling and the Icelandic Bank Collapse - Hannes Hólmsteinn Gissurarson 1953- (2014)
UK Chancellor Alistair Darling played an important role in the 2008 Icelandic bank collapse, refusing to include Icelandic-owned banks in the UK in the immense rescue package for British banks, closing them instead, and imposing an anti-terrorism law on Iceland. His hostility to Iceland is demonstrated in many places in his 2011 book on the international financial crisis. He wrongly asserts that Icelandic bankers donated money to the Conservative Party, and that Icelandic officials travelled around in jumbo jets. He also makes unfounded statements such as that Iceland was becoming insolvent in 2008, that the Icelandic Prime Minister had preferred a Russian loan to participating in an IMF programme and that the Prime Minister had tried to negotiate down payments requested from Iceland to the UK. In the midst of the crisis, Mr. Darling gave an inaccurate account publicly of a conversation with the Icelandic Finance Minister, as a House of Commons committee later concluded. What caused Darling’s hostility towards the Icelanders? Possibly two facts: in the UK, the Icelandic banks competed fiercely with traditional banks, thus causing resentment; and Iceland was before the collapse held up as a model by the Scottish nationalists to whom Mr. Darling was, and is, strongly opposed.